2005
DOI: 10.2200/s00004ed1v01y200508sap001
|View full text |Cite
|
Sign up to set email alerts
|

Articulation and Intelligibility

Abstract: Immediately following the Second World War, between 1947 and 1955, several classic papers quantified the fundamentals of human speech information processing and recognition. In 1947 French and Steinberg published their classic study on the articulation index. In 1948 Claude Shannon published his famous work on the theory of information. In 1950 Fletcher and Galt published their theory of the articulation index, a theory that Fletcher had worked on for 30 years, which integrated his classic works on loudness an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
46
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 71 publications
(180 reference statements)
0
46
0
Order By: Relevance
“…[6]) but this is probably the first attempt to use it for combination of information coming from different acoustic streams. Furthermore, under some assumption, DS combination rule is similar to what is known in the speech recognition community as the Fletcher's "product of errors" (see [7], [8]). …”
Section: Introductionmentioning
confidence: 97%
“…[6]) but this is probably the first attempt to use it for combination of information coming from different acoustic streams. Furthermore, under some assumption, DS combination rule is similar to what is known in the speech recognition community as the Fletcher's "product of errors" (see [7], [8]). …”
Section: Introductionmentioning
confidence: 97%
“…The AI measure is a sufficient statistic, composed of the average SNR in critical bands, expressed in dB. In 1921, Fletcher showed that the total average phone error is the product of critical band errors, and showed that P e 1 À P c ¼ e AI min (Allen, 2005b;Fletcher, 1921;French and Steinberg, 1947). Thus, the AI is an objective measure that is proportional to the average log phoneme error (Appendix A of Li et al (2010)).…”
Section: Introductionmentioning
confidence: 99%
“…Monaural speech segregation, which is the task of speech segregation from monaural recordings, is important for many real-world applications including robust speech and speaker recognition, audio information retrieval and hearing aids design (see e.g., [1], [7]). However, despite decades of effort, monaural speech segregation still remains one of the hardest problems in signal and speech processing.…”
mentioning
confidence: 99%